ANALISIS PERMINTAAN MIE INSTAN INDOMIE KOMODITAS TERKAIT DI KOTA KECAMATAN KABUPATEN SUKOHARJO - Moechamad Nasir (Benefit: Jurnal Manajemen dan Bisnis, 2004)
This research was intended to analysis factor that affect demand of the Indomie instant noodle inKartasura, Grogol and Sukoharjo districts of Sukoharjo Regency, the result of the study could indicatethat the Indomie instant noodle was kind of luxury, normal, or inferior goods. The result of analysisindicated that Indomie instant noodle was normal goods in three districts of Sukoharjo Regency basedon income elasticity; whereas own price elasticity of demand indicated the demand of Indomie noodle wasinelasticity for Kartasura, Grogol, Sukoharjo districts. The cross price elasticity of demand indicatedsubstitute commodity or complementary commodity for Indomie and related commodity in three districtsof Sukoharjo Regency. This research recomendation that increasing price of Indomie for districts whichthe demand of Indomie instant noodle was elasticity to get high revenue total, whereas for districts whichthe demand of Indomie instant noodle, was inelasticity to growing up marketing, means to increasequantity buying if Indomie instant noodle it is important to applaied decreasing price.